2003
DOI: 10.1046/j.1440-1797.2003.00134.x
|View full text |Cite
|
Sign up to set email alerts
|

Potassium depletion in a healthy north‐eastern Thai population: No association with tubulo‐interstitial injury

Abstract: Potassium depletion prevails among the healthy population of north-east Thailand, as well as among patients with certain metabolic disorders such as upper urinary tract stones, the sudden unexplained death syndrome, distal renal tubular acidosis and hypokalaemic periodic paralysis. However, definite proof of the relationship of potassium depletion and these metabolic disorders is lacking. We prospectively studied muscle and kidney potassium content including renal tissue pathology in three groups of healthy ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…Our recent study analyzing muscle K contents in cadaveric subjects, who resided in the northeastern part of Thailand and died from vehicle accident, revealed that approximately 23% of the recruited subjects (7 out of 30 cases) had K depletion (K < 80 µmol/g wet weight), 6 consistent to the previous surveys, which indicated that the northeastern part of Thailand is a high prevalent area of K deficiency. 7,8 This population was therefore our focus in the present study aiming for analyzing changes in proteome profile of skeletal muscle in human subjects when muscle K was chronically depleted. Specimens were collected within 6 h of death to obtain the most reliable data.…”
Section: Introductionmentioning
confidence: 99%
“…Our recent study analyzing muscle K contents in cadaveric subjects, who resided in the northeastern part of Thailand and died from vehicle accident, revealed that approximately 23% of the recruited subjects (7 out of 30 cases) had K depletion (K < 80 µmol/g wet weight), 6 consistent to the previous surveys, which indicated that the northeastern part of Thailand is a high prevalent area of K deficiency. 7,8 This population was therefore our focus in the present study aiming for analyzing changes in proteome profile of skeletal muscle in human subjects when muscle K was chronically depleted. Specimens were collected within 6 h of death to obtain the most reliable data.…”
Section: Introductionmentioning
confidence: 99%